Возможно только если ты местами перепутал
Объяснение:
Если двойка это степень
y^2-8y+17>0
y^2-8y>-17
y(y-8)>-17
y>-17 y>-17-8
y>-25=> Не доказано
Если 2 имеется ввиду множитель 2y, то
2y-8y+17>0
-6y+17>0
-6y>-17
6y>17
y=17/6
y=
y=2
Возможно только если ты местами перепутал
Объяснение:
Если двойка это степень
y^2-8y+17>0
y^2-8y>-17
y(y-8)>-17
y>-17 y>-17-8
y>-25=> Не доказано
Если 2 имеется ввиду множитель 2y, то
2y-8y+17>0
-6y+17>0
-6y>-17
6y>17
y=17/6
y=![\frac{17}{6}](/tpl/images/1162/9903/6c9fa.png)
y=2![\frac{5}{6}](/tpl/images/1162/9903/2bbce.png)